ACTUAL NUTRITION AND PHYSICAL DEVELOPMENT OF HIGH SCHOOL STUDENTS (In the Case of Karshi and Kitab Cities) - Gofurova J. T. (European Science Publishing, 2024)
The paper presents the results of an assessment of the social nutrition practices of high school students. The study involved 256 girls and boys aged 15–17 years – students of general education institutions in the city of Karshi and Kitab. The study included: studying the state of the body's supply of nutrients and energy (nutritional status); assessing the risk of developing eating disorders and types of eating disorders; determination of actual food consumption. The data obtained indicate a high prevalence of eating disorders among schoolchildren of the overeating type. It was found that 40,2 % of schoolchildren of both sexes have risky eating behavior. It is shown that the externalized type of eating behavior is more common among high school students, and the restrictive and emotiogenic types are less common. Violations of food consumption by schoolchildren have been revealed, which manifest themselves in non-compliance wi
Keywords: schoolchildren, Karshi and Kitab city, social nutrition practices, nutritional status, eating behavior, actual consumption of food and food substances.